Audience Perception of the Elderly in Nollywood Films - Subulola Etimiri; Omotola Ogunbola; Omolara Akin-Odukoya; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This study is an assessment of Audience Perception of the Elderly in Nollywood Films. The general objective of this study is to examine how Nollywood Films affect how people see the elderly in society. The study examines how film perpetuates age stereotypes among the elderly. Some of the determined objectives are to examine how movie representation of the elderly shapes audience perception of old people in Nigeria. Data for this study was obtained through content analysis, in-depth interviews, and questionnaires. Screen Theory and Reflection Projection Theory were the theories used for this project. Content analysis was carried out on four films: Maami, October 1, Kasanova, and Ayelujara. An in-depth interview was conducted with two lecturers at Caleb University, Imota, Lagos, and questionnaires were distributed to 84 students of the school. This research work established that the portrayal of the elderly in Nollywood films has succeeded in influencing how viewers perceive the elderly. It also established that Nollywood Films have a significant influence on the audience's perception of the elderly and film as a medium is very vital and goes beyond merely seeing it as entertainment such as creating mindset, opinions, culture and life in general.